THE EFFECT OF GRAPHIC ORGANIZERS, GUIDED WRITING STRATEGIES, AND READING LEVELS ON THE WRITING ACHIEVEMENT OF THE FOURTH SEMESTER STUDENTS OF PGMI PROGRAM AT IAIN RADEN INTAN LAMPUNG - SEPTY ANGGRAINY; CHUZAIMAH D. DIEM; MACHDALENA VIANTY; BASTIAN SUGANDI (Sriwijaya University Learning and Education International Conference, 2016)
The strategies are needed in teaching process; the teacher must decide the strategies bestsuited for the writing skills of each process. Therefore, Graphic Organizers and GuidedWriting strategies are strategy to assist the students in writing process. The objectives of thestudy were aimed in improving the student’s writing achievement by using Graphic Organizerand Guided Writing strategies and highlighting the significant interaction effect of GraphicOrganizers and Guided Writing strategy and Students’ Reading Levels on WritingAchievement. Sixty students of PGMI Program at IAIN Raden Intan Lampung were chosenrandomly based on their reading levels. The data were collected through pretest and posttest.The result showed that there was a significant difference in writing achievement after theywere taught by using Graphic Organizer and they were taught by Guided Writing and betweenthe students who were taught by using Graphic Organizer group and those who were taughtby Guided Writing strategies.